Trial of IFN or STI571 before proceeding to allografting for CML? - Hehlmann, Rüdiger (Leukemia, 2000)
Ten-year survival of IFN-treated low risk CML patients is about 40%, and more in cytogenetic responders. Allografting has a cure rate of up to 75%, but is associated with considerable procedure related morbidity and mortality. One out of three or four is likely not to survive. A comparative quantification of survival after BMT and IFN treatment suggests that a trial of IFN (and possibly STI 571) before proceeding to allografting is a viable, and in low risk patients a probably preferable option.
Gesehen am 19.05.2022